The identity and role of stakeholders in the medical tourism industry: state of the art - Kamassi, Ahmed; Abd Manaf, Noor Hazilah; Omar, Azura (Emerald Group Publishing Ltd., 2020)
Purpose: This paper aims to address and identify the major stakeholders in the medical tourism industry, based on their participation in medical tourism activities and their support for medical tourism development.